ANALISIS NILAI PELANGGAN DAN KEBIJAKAN TARIF LISTRIK PRABAYAR TERHADAP KEPUASAN PELANGGAN PT PLN BRIGHT BATAM - Renniwaty Siringoringo (JURNAL AKUNTANSI BARELANG, 2019)
Prepaid electricity information technology services inovation by PT PLN, that aims to effectively and simplify to accesing and managing electricity usage, but this not responded positively by people in Batam. This is evident from the number of pre-paid electricity customers who are still far from the target of PT PLN, amount of complaints of tariff that differ from usage, and the problem rotating electricity power off. This research aims to measure the effect of customer value and price or tariff to customer satisfaction PT PLN Bright Batam.Quistionaire was used as main data collection instrument. Total respondent are 100 that have used prepaid electricity at Batam Centre sub district. Data was analysed using Multiple Linier Regression.The result showed that customer value and price or tariff have positive and significant effect, with R2 79,1%. Partially, customer value and price or tariff have positive and significant effect to costumer satisfaction.